The Potential of α- glucosidase Inhibition from Endophytic Fungi Associated in Portulaca oleracea L - Siska,; Suhaenah, Asriani; Latuconsina , Saripa Indira Syahraini (Ad-Dawaa' Journal of Pharmaceutical Sciences, 2023)
Introduction: The discovery of endophytic microbes, which are microorganisms that reside within plant tissues and can produce bioactive compounds with similar properties to their host plants, is one possible solution to this issue. Endophytic fungi are capable of manufacturing antibacterial, antifungal, antiviral, anticancer, antimalarial, and antidiabetic agents. Portulaca oleracea L. is a weed that has spread globally. Portulaca oleracea L.has been utilized as a nutritious and medicinal plant for countless centuries. Aims: This study seeks to assess the antidiabetic potential of the endophytic fungi Portulaca oleracea L. Methods: In this study, isolation, macroscopic testing, fermentation, and antidiabetic activity testing were conducted using the alpha-glucosidase method. Twelve isolates with macroscopically distinct characteristics were obtained from of isolating the endophytic fungi. The procedure then advances to the fermentation and ethyl acetate extraction phases. Result: The results showed that there was inhibition of the α-glucosidase enzyme in hydrolyzing substrates into glucose by secondary metabolite extracts of fungi associated with the plant Portulaca oleracea L. with the highest percentage inhibition on the lab scale in the 12th isolate (83.92%). Conclusion: This measurement gives good results as an α-glucosidase inhibitor, so its potential as a source of antidiabetic drug substances is very high.